Leadership of learning and change for successful learning outcome in History Education - Hennades Tabe; Jan Heystek; Pieter Warnich (Perspectives in Education, 2021)
Managing History learning and teaching in schools of South Africa over the years has been characterised by diverse opinions regarding the causes of learner underperformance, who is to be held responsible over learner performance and possible leadership influence on History learner performance. In addressing the problem of underperformance in History from a leadership point of view, the researchers were guided by the managerial leadership and humanism learning theories. The selected qualitative methodology adopted an ethnographic design to establish hidden inferences. A sample of thirty participants comprising the provincial coordinator for History, subject advisor, principals, departmental heads, teachers and learners was obtained based on the availability of History-offering schools in the study area. Data collection was mainly through interviews and meta-analysis of documents. Both deductive and inductive reasoning was applied using ATLAS.ti version 8.4 and thematic analysis in the data analyses process. The findings suggest several managerial leadership measures ranging from policy to practice. These amongst others include the recommendation that History as part of social science should be separated in totality from Geography.